Qualidade, compostos bioativos e atividade antioxidante de variedades de videiras do Banco Ativo de Germoplasma da Embrapa Semiárido - Batista, Patrício Ferreira (Universidade Federal Rural do Semi-Árido, 2014)
Modern society is increasingly searching for foods that can treat and prevent diseases and increase longevity. Among these it stands out the functional foods, including beverages, rich in antioxidants with proven beneficial effects to health, as grapes and their derivatives. In view of this, a study was carried out in order to identify grape varieties suitable for consumption in natura and processing which, besides meeting the requirements of commercial quality, have high contents of compounds with functional properties. In the study it was used grape clusters harvested from the Active Grape Germplasm Bank plants grown at the Mandacaru Experimental Field, Embrapa Semiarid, Juazeiro, state of Bahia, Brazil. It was evaluated 31 grapevine varieties in the crop cycles of the first and second semesters of 2011, that is, A dona, Barbera, Benitaka, Blue Lake, Brasil, Cardinal, Christmas Rose, Estevão Marinho, Frankenthal, Gamay, Grenache, Isabel, Isabel Precoce, Isaura, Liberty, Máximo, Moscato Caillaba, Moscato de Hamburgo, Moscato Noir, Patrícia, Piratininga, Royalty, Saturn, Scarlet, Syrah 1 (a clone from France), Syrah 2 (a clone from the state of Rio Grande do Sul), Tampa, Tannat, Tibouren, Traviú, and Vênus. The traits evaluated in the fruits were skin color, resistance to compression, soluble solids (SS), titratable acidity (TA), SS/TA ratio, tannins (dímeric, oligomeric and polymeric), total extractable polyphenols (TEP), total anthocyanins, yellow flavonoids, condensed tannins, and antioxidant activity by using DPPH and ABTS methods. The generalized Mahalanobis distance was used for quantifying the genetic divergence between the varieties. As strategies of clustering, it was used UPGMA and analysis of canonical variables. The cluster analysis resulted in five groups of varieties. The varieties Cardinal and Royalty showed high genetic diversity between themselves, thus suitable for insertion into breeding programs aiming at exploring the variability of the Active Germplasm Bank of Embrapa Semiarid. The varieties Royalty and Máximo, suitable for processing, stood out by presenting high levels of tannins (dimeric, oligomeric and polymeric), TEP, total anthocyanins, yellow flavonoids and total antioxidant activity. Among the varieties with different aptitudes, Tampa stood out with high contents of total anthocyanins and yellow flavonoids. Contents of TEP and condensed tannins were intimately correlated with the antioxidant activity of the grapes. The results obtained in this study constitute the basis for the formation of a bank of traits related to grape bioactive compounds
Quality, bioactive compounds, and antioxidant activity of grape varieties from the Active Germplasm Bank of Embrapa Semiarid
Keywords: Vine; Bioactive compounds; Antioxidant activity; Tropical viticulture; Videira; Compostos bioativos; Atividade antioxidante; Viticultura tropical; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA